THE INTERNATIONAL STANDARDS IN FIELDS OF APPLICATION OF INFORMATION TECHNOLOGY - Predrag DASIC; Zivadin MICIC (Fiabilitate şi Durabilitate)
According International Classification for Standards (ICS) Application of Information Technology is ranged in frame of group ICS=35.240, with 280 ISO or ISO/IEC and 45 IEC standards. In the paper is presented analysis of ISO, ISO/IEC and IEC standards for Application of Information Technology and structure Technical Committee (TC) for fields of Information Technology